Modeling by artificial neural networks of the performance indicators of the operation of a downdraft thermochemical gasifier - Gutierrez Gualotuña, Eduardo Roberto (2019)
The research results are presented by the authors in the modeling of performance indicators of the operation of biomass gasification installations using artificial neural networks, starting by the classification of the information derived from the systemic analysis of its operation. A bibliographical study of previous related researches was developed. A 3N experimental plan with 3 replicas is made in order to generate four models according to their own performance indicators using neural networks. The quality indicators of the neural networks are compared with those obtained by nonlineal regression models. As biomass the Oryza sativa is used